Microbiome Clusters Disclose Physiologic Variances in Dairy Cows Challenged by Calving and Lipopolysaccharides - Johanna Tröscher-Mußotter (American Society for Microbiology, 2021)
The health of dairy cows has to be carefully considered for sustainable and efficient animal production. The microbiome of animals plays an important role in the host’s nutrient supply and regulation of immune functions.